Star-planet interactions and selection effects from planet detection methods - Poppenhaeger, K; J H M M Schmitt (arXiv.org, 2013)
Planets may have effects on their host stars by tidal or magnetic interaction. Such star-planet interactions are thought to enhance the activity level of the host star. However, stellar activity also affects the sensitivity of planet detection methods. Samples of planet-hosting stars which are investigated for such star-planet interactions are therefore subject to strong selection effects which need to be taken into account.